PUNAHNYA SENTRA INDUSTRI GERABAH YANG TERLAMBAT BERINOVASI TIDAK SELARAS DENGAN PERKEMBANGAN JAMAN DAN TEKNOLOGI (STUDI KASUS PADA SENTRA INDUSTRI KECIL GERABAH DI DESA NGUNUT, POJOK, TLADAN, GARON KEC. KAWEDANAN KAB. MAGETAN JAWA TIMUR) - HARI PURWANTO; DIAN CITANINGTYAS ARI KADI (LP2MTBM MAKARIOZ, 2020)
The purpose of this case study is to examine the factors that caused the extinction of the pottery industry center and findimprovement solutions if it still allows the industry to be re-run. This research approach is qualitative with case studies. Theinformants included potters, potters, local village equipment and local communities. Data analysis includes (1) data collection(2) data display (3)data reduction and (4) conclusions. (Miles, Mathew B., 1994) The results showed that there are five mainproblems that cause the extinction of the pottery industry center, among others; (1) Market demand decreases due to its rolein being replaced by goods made by manufacturers of solutions by highlighting the copetitive advantages of natural claymaterials in other earthenware functions(2) Late innovating and transfer of the function of the production of the solution byinnovating and switching from the power of the gera functionbah into the value of pottery (3) The production process isuntouched advanced technology solutions with advanced technology approaches and information technology (4) Entangledmiddle-class businesses have difficulty getting capital for the development of solutions Need a joint institution can be in theform of cooperatives or groups ( 5) The role of the government that has not been maximal solution maximizes the role of thegovernment.